Unmasking Occult Malignancy: The Pivotal Role of the Peripheral Blood Smear in the Initial Diagnosis of Chronic Lymphocytic Leukemia - Agustinus Sigit Pamungkas; Enny (HM Publisher, 2025)
Background: Chronic lymphocytic leukemia (CLL) is a common hematologic malignancy in adults, frequently discovered incidentally through routine blood tests due to its often nonspecific clinical presentation. In resource-limited settings, fundamental laboratory investigations are crucial for initiating the diagnostic pathway. This report illustrates the critical diagnostic value of the complete blood count and peripheral blood smear in identifying CLL in a patient presenting with vague constitutional symptoms. Case presentation: A 43-year-old female with a history of type 2 diabetes mellitus presented to a rural hospital with a one-month history of debilitating fatigue, intermittent fever, and loss of appetite. Physical and radiological examinations were unremarkable. However, initial hematological analysis revealed marked leukocytosis (77,910/μL), mild anemia, and thrombocytopenia (54,000/μL). A peripheral blood smear was pivotal, showing an absolute lymphocytosis of 90% with mature-appearing lymphocytes, pleomorphism, and characteristic smudge cells. Following referral, definitive diagnosis was established through flow cytometry, which confirmed a clonal B-cell population (CD19+, CD5+, CD23+, dim CD20+). Bone marrow examination showed extensive infiltration, and molecular studies revealed an unmutated IGHV gene status, placing the patient in a high-risk prognostic category. Conclusion: This case underscores that even in the absence of advanced diagnostic facilities, a meticulous evaluation of the peripheral blood smear is a powerful and essential tool for unmasking serious underlying hematologic malignancies like CLL. It enables early suspicion, appropriate patient referral, and timely initiation of management, thereby significantly impacting patient outcomes.